Pengaruh Penggunaan Metode Diskusi Terhadap Peningkatan Hasil Belajar Bahasa Indonesia - Ganna, Resty Palilu; Dewi, Resnita; Baan, Anastasia (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to find out how students' communication skills during discussions can have an influence on student learning outcomes, as well as knowing student learning outcomes, and to find out the significant influence between teacher communication skills on the learning outcomes of class XI students at SMKN 1 Tana Toraja. This research is a quantitative descriptive research with the type of research using a field survey. Data collection techniques in this research used observation, questionnaires, interviews and documentation. The data analysis technique in this research is Product moment correlation. The results of this research can be concluded that students' communication skills in the discussion method have a good influence with a percentage of 65% and student learning outcomes are sufficient with a percentage of 35%. There is a significant influence between students' communication skills on learning outcomes in the Indonesian language subject class XI SMKN 1 Tana Toraja. Hypothesis testing is as follows: where ro = 0.005 is greater than r table at a significance level of 5% = 0.396, thus Ha is accepted and HO is rejected. This means that the better the students' ability to communicate, the better the grades obtained by students at SMKN 1 Tana Toraja.